Diversity, Utilization and Management of Medicinal Plants in Baitadi and Darchula Districts, Far West Nepal - Kunwar, Ripu M; Chowdhary, Chotte L; Bussmann, Rainer W (The Initiation, 2010)
As in other districts of Nepal, medicinal plants have played a significant role in the life of local people of Baitadi and Darchula districts by providing products for trade, subsistence and traditional therapies. Present study analyzed the pharmacological activities of the species which had the highest informant consensus factor. The use of Asparagus racemosus as galactogogue with consensus factor 0.97, Berberis asiatica for eye troubles with 1.0, Cordyceps sinensis as tonic and longevity with 0.97, Curculigo orchoides as tonic and aphrodisiac with 0.96, Nardostachya grandiflora for epilepsy with 0.97 and Phyllanthus emblica as diuretic with 0.97 possessed the highest consensus factors and greatest affinity to the Ayurveda and phytochemical findings. Phytochemical screening and validity assessments of the medicinal plant widely used in traditional therapies are worthwhile. The findings with the maximum affinity of informant consensus factors and phyto-chemical validations provide the potential to identify which plants are most likely to be useful in the treatment of diseases. Key Words: Medicinal plants, Ethno-medicine, Informant consent factor (ICF), Phyto-chemical validation, West Himalaya DOI: 10.3126/init.v2i1.2538 The Initiation Vol.2(1) 2008 pp157-164